olymorphism and Expression of Drug resistance Genes in Colorectal Cancer Patients Given Adjuvant Folfox-4 Chemotheraphy - Mirakhrli, Mogjan (2011)
Failed chemotherapy is a major obstacle to apply adequate high doses of drugs in eliminating tumor cells. The detection of markers that predict drug resistance is of major interest in selecting the likely effective medications in first-line treatment. Colorectal cancer (CRC) is intrinsically resistant to chemotherapy. This limits the effectiveness of current anticancer drugs. But variable responses can be expected in chemotherapy with the same medications. Thereby, reliable predictive molecular markers will help oncologists to identify patients who are at risk of non-response to chemotherapy. ATP-binding cassette (ABC) multidrug transporters mediate to export many clinically important drugs, hence preventing accumulation of effective dosage of drugs in cancerous cells. As a result, there is great interest in the study of members of the ABC multidrug transporters in chemo-resistance. This hospital-based study, for the first time, aimed to examine the putative association of single nucleotide polymorphisms (SNPs) and the protein expression of drug resistance-associated markers in response to platinum-base adjuvant chemotherapy in a homogeneous CRC (II/III) population. Herein, three common members of ABC multidrug transporters that relate in exporting platinum agents were studied including; multidrug resistance protein 1 (MRP1), multidrug resistance protein 2 (MRP2), and multidrug resistance 1(MDR1). The study was carried out on 50 patients who did not receive preoperative chemotherapy and radiotherapy and treated with adjuvant FOLFOX-4 (oxaliplatin+5FU/LV) chemotherapy. Clinicopathologic parameters were obtained from hospital records. Range of follow up was 24-48 months and patients who stopped their treatment were excluded from the study. Fifteen cases showed relapse within one year of follow up of which 5 developed recurrences at time of chemotherapy (within 6 months). Protein expression of paraffin embedded tumor tissues and their corresponding normal mucosa were detected by immunohistochemistry staining. In addition, SNPs (MDR1 C3435T, G2677T/A, T129C, MRP1 G2168T, G1299T and MRP2, G1249A, C-24T and C3972T) that are likely able to influence protein expression and consequently alter function of proteins were examined in the present study. The role of those SNPs in CRC development and tumorgenesis was also investigated in a case-control study using blood samples of 50 age-gender matched healthy individuals. Isolated DNA from paraffin embedded tumor tissues, corresponding normal tissues, and blood samples were genotyped using RFLP-PCR and SSCP-PCR methods. The Kaplan-Meier method was used to adjust survival times with each factor.Interestingly, the MRP2-positive was observed in 24 (48%) and 7 (14%) cases of the tumor and the corresponding normal mucosa, respectively (p=0.003). The incidence of recurrence and metastasis for patients in the positive expression group of three proteins was not higher than that in the MRP1-negative expression group (p>0.05). We identified a subpopulation (n=5) with MRP2-positive among patients with recurrence as a subset of patients with a poor prognosis that they demonstrated recurrence at time of chemotherapy (p=0.022). No differences were also observed in the genotypic frequencies between the patients with early relapse and those who remained event-free (all p>0.05). However, patients with mutant allele T and A of 2677 and 1249 significantly had high disease-free survival and overall survival compared to patients with wild allele G and G (p=0.045; p=0.044). Additionally, correlation between SNPs and positive expression of three biomarkers was not observed. In conclusion, the polymorphisms of three genes are not a risk factor for CRC development among Iranians. Furthermore, the expression of three proteins in neoplastic tissue did not influence the prognosis of the disease. G2677T and G1249A polymorphisms are associated with disease-free survival time and overall survival in patients treated with FOLFOX-4 chemotherapy after surgery resection (p<0.05). In addition, G2677T MDR1 polymorphisms may relate to gender of CRC patients. Further studies in a larger population must be necessary to reach more reliable conclusion.